HUBUNGAN PENDIDIKAN DENGAN STATUS GIZI IBU SELAMA HAMIL DI PUSKESMAS MUSUK I - Pamungkas, Atik Mahmudah; Nurlaili, Helmi (Jurnal Kebidanan, 2024)
The background of this study is the nutritional status of mothers during pregnancy which can be influenced by several factors. The nutrition of pregnant women is one of the focuses of community nutrition improvement activities because of its significant impact on the condition of the fetus they are carrying. Nutritional problems that are often encountered in pregnant women are chronic energy deficiency (CED). The average level of education of the Indonesian population, especially women, is still low, this has an impact on health, encouraging infectious diseases and malnutrition. The 2018 Basic Health Research (Riskesdas) showed that the prevalence of CED risk in pregnant women (15-49 years) was still quite high, namely 17.3%. The percentage of pregnant women with CED is expected to decrease by 1.5% each year. The purpose of this study was to determine the relationship between education and maternal nutritional status during pregnancy at the Musuk I Health Center. The design of this study used a quantitative descriptive research type using a retrospective approach, the population technique used simple random sampling in the chi-square method, the population was 430 people who came from January to December 2023, using the slovin formula, a sample of 81 respondents was found. Research Results There is a significant relationship between maternal education and maternal nutritional status during pregnancy at the Musuk I Health Center. The results of the chi-square test obtained a value of ρ value = 0.046 <ɑ = 0.05, which means that there is a relationship between maternal education and maternal nutritional status during pregnancy at the Musuk I Health Center.